Strictly co-isogenic C57BL/6J-Prnp(−/−) mice: A rigorous resource for prion science - Nuvolone, Mario (J Exp Med, 2016)
Although its involvement in prion replication and neurotoxicity during transmissible spongiform encephalopathies is undisputed, the physiological role of the cellular prion protein (PrP(C)) remains enigmatic. A plethora of functions have been ascribed to PrP(C) based on phenotypes of Prnp(−/−) mice. However, all currently available Prnp(−/−) lines were generated in embryonic stem cells from the 129 strain of the laboratory mouse and mostly crossed to non-129 strains. Therefore, Prnp-linked loci polymorphic between 129 and the backcrossing strain resulted in systematic genetic confounders and led to erroneous conclusions. We used TALEN-mediated genome editing in fertilized mouse oocytes to create the Zurich-3 (ZH3) Prnp-ablated allele on a pure C57BL/6J genetic background. Genomic, transcriptional, and phenotypic characterization of Prnp(ZH3/ZH3) mice failed to identify phenotypes previously described in non–co-isogenic Prnp(−/−) mice. However, aged Prnp(ZH3/ZH3) mice developed a chronic demyelinating peripheral neuropathy, confirming the crucial involvement of PrP(C) in peripheral myelin maintenance. This new line represents a rigorous genetic resource for studying the role of PrP(C) in physiology and disease.